EFEKTIVITAS PROGRAM PENDIDIKAN MAGANG DALAM MENGEMBANGKAN KOMPETENSI MAHASISWA BERDASARKAN CAPAIAN PROFIL LULUSAN FAKULTAS TARBIYAH UNIVERSITAS TAZKIA - Suci Hermalia Utami; Asnan Purba (JURNAL TARBIYAH, 2025)
This study aims to determine the effectiveness of the internship program in developing student competencies based on the achievement of the profile of graduates of the Faculty of Tarbiyah, Tazkia University. The internship program is a means of experiential learning that supports students in applying knowledge directly in the world of education. This research uses a descriptive quantitative approach with data collection techniques through questionnaires. Data analysis was carried out by testing validity, reliability, classical assumptions, simple linear regression, coefficient of determination, and t test. The results showed that the internship program had a significant effect on student competence. The significance value of 0.000 <0.05 indicates a significant relationship between the internship program and student competence. The coefficient of determination (R Square) of 0.848 means that 84.8% of variations in student competence can be explained by the internship program. Thus, the internship program is considered effective in developing student competencies, especially in pedagogical, professional, personality, and social aspects. This program can be an important strategy in supporting graduate learning outcomes in accordance with national standards of higher education.